The Impact of E-Commerce on the Business Development of Muslim Traders in the Traditional Market of Butung, Makassar City From the Perspective of Islamic Economics - Muh. As’ad Rusydi Al-Hadar; Muslihati Muslihati; Idris Parakkasi (Al-Fadilah: Islamic Economics Journal, 2025)
The current business trading pattern is very common especially in traditional markets as we know that E-Commerce is one of the platforms for selling and marketing products but in the use of E-Commerce, of course, it has positive and negative impacts on its use as is the case in the traditional Butung Market in Makassar city. In the problems that occur, the problem formulated in this study is how the mechanism of using E-Commerce by Muslim traders in the Butung market in Makassar city based on Islamic economic perspectives and how the impact of E-Commerce on the business development of Muslim traders in the Butung market in Makassar city. The purpose of this research is to find out how the mechanism of using E-Commerce by Muslim traders in the butung market of Makassar city if seen from the perspective of Islamic economics and to find out how the impact of business development from the use of E-Commerce on Muslim traders in the butung market of Makassar city. The results of this study indicate that 3 of the informants who have been interviewed have a positive impact on the use of E-Commerce in this case helping to increase sales and 2 of the informants make E-Commerce a challenge due to limited facilities and infrastructure in the use of E-Commerce.